2011 18th IEEE International Conference on Image Processing 2011
DOI: 10.1109/icip.2011.6115673
|View full text |Cite
|
Sign up to set email alerts
|

Transform domain sparsification of depth maps using iterative quadratic programming

Abstract: Compression of depth maps is important for "texture plus depth" format of multiview images, which enables synthesis of novel intermediate views via depth-image-based rendering (DIBR) at decoder. Previous depth map coding schemes exploit unique depth data characteristics to compactly and faithfully reproduce the original signal. In contrast, since depth map is only a means to the end of view synthesis and not itself viewed, in this paper we explicitly manipulate depth values, without causing severe synthesized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 14 publications
0
34
0
Order By: Relevance
“…For example, depth pixels close to an object edge are likely to affect synthesized view distortion more than depth pixels interior to an object. Exploiting this observation, [6] optimized mode selection during H.264 coding of depth video, while [5] manipulated unimportant depth pixels (without causing severe synthesized view distortion) towards a sparse representation of the depth signal in the transform domain. In contrast, our work exploits the unique characteristics of depth maps (sharp edges and smooth interior surfaces) for coding gain.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, depth pixels close to an object edge are likely to affect synthesized view distortion more than depth pixels interior to an object. Exploiting this observation, [6] optimized mode selection during H.264 coding of depth video, while [5] manipulated unimportant depth pixels (without causing severe synthesized view distortion) towards a sparse representation of the depth signal in the transform domain. In contrast, our work exploits the unique characteristics of depth maps (sharp edges and smooth interior surfaces) for coding gain.…”
Section: Related Workmentioning
confidence: 99%
“…While compression of texture maps is well studied, compression of depth maps is relatively new, and has been the focus of many recent research efforts [3,4,5]. Typical depth maps exhibit unique characteristics, such as sharp edges and smooth surfaces interior to the sharp edges, that are quite different from texture maps, and previous depth map compression algorithms have attempted to exploit these characteristics for coding gain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We leverage the recent results by Cheung et al 7 to derive weights of importance for individual MBs in a depth frame.…”
Section: Related Workmentioning
confidence: 99%
“…6, 7 These studies 6,7 observed that depth maps are encoded solely for the purpose of view synthesis and designed specialized coding optimization accordingly. In one work, 6 coding modes in H.264 are selected based on individual MBs' impact on synthesized view distortion.…”
Section: Related Workmentioning
confidence: 99%